2022
DOI: 10.3390/v14122753
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Protein C Signaling System Is Associated with COVID-19 Hypercoagulability—A Single-Cell Transcriptomics Analysis

Abstract: Because of the interface between coagulation and the immune response, it is expected that COVID-19-associated coagulopathy occurs via activated protein C signaling. The objective was to explore putative changes in the expression of the protein C signaling network in the liver, peripheral blood mononuclear cells, and nasal epithelium of patients with COVID-19. Single-cell RNA-sequencing data from patients with COVID-19 and healthy subjects were obtained from the COVID-19 Cell Atlas database. A functional protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Several studies focus on COVID-19 patients' increased thromboembolic risk. Protein C could play a mechanistic role in the hypercoagulability syndrome affecting patients with severe COVID-19 [41]. The overwhelming inflammatory response in patients with SARS-CoV-2 infection can lead to a hypercoagulable state [42].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies focus on COVID-19 patients' increased thromboembolic risk. Protein C could play a mechanistic role in the hypercoagulability syndrome affecting patients with severe COVID-19 [41]. The overwhelming inflammatory response in patients with SARS-CoV-2 infection can lead to a hypercoagulable state [42].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find active viral replication in cell culture (Figure 3A). Nevertheless, as our previous study suggested, protein C could play an important role in hypercoagulability in severe COVID-19 (Silva, Jara et al 2022). We asked whether treatment of ECs with PC before exposure to SARS-CoV-2 infection could result in a protective endothelial effect.…”
Section: Pc Pretreatment Reduces the Expression Of Ccl2 Il6 And Serpi...mentioning
confidence: 95%
“…Datasets were retrieved from Gene Expression Omnibus (GEO) and the European Genome-phenome Archive (EGA) under accession numbers GSE171668 and EGAS00001004344, respectively. The raw data with the .h5 format were processed using the standard toolkit Scanpy 1.7.2 in Python igraph 0.9.6. processing and quality control flow previously described (Silva, Jara et al 2022) and available at https://scanpy-tutorials.readthedocs.io/en/latest/pbmc3k.html. Data were then integrated using Harmony's algorithm, which designs cells in a shared embedding grouped by cell type (Korsunsky, Millard et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…aPC can suppress thrombin formation by proteolytical degradation or inactivation of coagulation factor Va (FVa) and FVIIIa and increases fibrinolytic activity by neutralizing PAI-1. However, the thrombin-thrombomodulin-EPCR complex is dysfunctional under COVID-19, affecting the aPC synthesis [ 113 , 114 ]. Also, an enhanced thrombin generation, decreased fibrinolytic activity, and elevated levels of PAI-1 were identified in patients with long-COVID [ 115 ].…”
Section: Disbalanced Endothelial-derived Hemostatic Regulators In Cov...mentioning
confidence: 99%
“…Stimulation of coagulation factors in DM may accentuate the risk of thrombotic events. In this sense, the thrombin-thrombomodulin-EPCR complex has been often observed dysfunctional under both DM and COVID-19, affecting aPC synthesis [ 113 , 114 ]. Therefore, COVID-19 and DM, by sharing or accumulating mechanisms of endothelial activation and dysfunction, may stimulate more severe vascular-driven complications than these entities alone.…”
Section: Diabetes Mellitus a Comorbidity In Covid-19mentioning
confidence: 99%